A kinetic study and thermal decomposition characteristics of palm kernel shell using model-fitting and model-free methods - Hussain, M. (Taylor and Francis Ltd., 2022)
The thermal decomposition behaviours of palm kernel shells (PKS) under non-isothermal conditions were investigated using the thermogravimetric analyser. A comparison of model-free and model-fitting methods for PKS decomposition was performed. Differential and integral methods used showed an increase in apparent activation energy with the conversion. Besides that, the global single reaction mechanism was evaluated using the reaction order and Sestak-Berggren models. Curve fitting results showed that Sestak-Berggrenâs model demonstrated that the PKS pyrolysis mechanism was better than the reaction order model. The components, namely moisture, hemicellulose, cellulose, and lignin were found to decompose simultaneously. From Kissingerâs method, the average activation energy for devolatilisation, cellulose, and hemicellulose were 24.65 kJ molâ1, 78.98 kJ molâ1, and 183.07 kJ molâ1, respectively. The decomposition of lignin occurred slowly, with a slower conversion rate in contrast to the hemicellulose and cellulose components.Highlights PKS pyrolytic kinetics were studied through KAS, FWO and Friedman methods. Model-free methods can predict lignocellulosic biomass components activation energies well. The three independent-parallel-reaction model fits well with experimental data. Â© 2019 Informa UK Limited, trading as Taylor & Francis Group.